A brief survey to identify pregnant women experiencing increased psychosocial and socioeconomic risk. Issue 3 (June 2019) - Price, Anna; Bryson, Hannah; Mensah, Fiona; Kemp, Lynn; Smith, Charlene; Orsini, Francesca; Hiscock, Harriet; Gold, Lisa; Smith, Ashlee; Bishop, Lara; Goldfeld, Sharon
Abstract: Problem: Identifying pregnant women whose children are at risk of poorer development in a rapid, acceptable and feasible way. Background: A range of antenatal psychosocial and socioeconomic risk factors adversely impact children's health, behaviour and cognition. Aim: Investigate whether a brief, waiting room survey of risk factors identifies women experiencing increased antenatal psychosocial and socioeconomic risk when asked in a private, in-home interview. Methods: Brief 10-item survey (including age, social support, health, smoking, stress/anxious mood, education, household income, employment) collected from pregnant women attending 10 Australian public birthing hospitals, used to determine eligibility (at least 2 adverse items) for the "right@home" trial. 735 eligible women completed a private, in-home interview (including mental health, wellbeing, substance use, domestic violence, housing problems). Regression models tested for dose-response trends between the survey risk factor count and interview measures. Findings: 38%, 31%, 15% and 16% of women reported a survey count of 2, 3, 4 and 5 or more adverse risk factors, respectively. Dose-response relationships were evident between the survey count and interview measures, e.g. of women with a survey count of 2, 8% reported ever having a drug problem, 4% experienced domestic violence in the last year and 10% experienced housing problems, contrasting with 31%, 31% and 26%, respectively, for women reporting a survey count of 5 or more. Discussion/Conclusions: A brief, waiting room survey of psychosocial and socioeconomic risk factors concurs with a private antenatal risk factor interview, and could help health professionals quickly identify which women would benefit from more support.